N(alpha)-tosyl-L-phenylalanine chloromethyl ketone induces caspase-dependent apoptosis in transformed human B cell lines with transcriptional down-regulation of anti-apoptotic HS1-associated protein X-1 - Jitkaew, Siriporn; Trebinska, Alicja; Grzybowska, Ewa; Carlsson, Göran; Nordström, Anders; Lehtiö, Janne; Fröjmark, Anne-Sophie; Dahl, Niklas; Fadeel, Bengt (The Journal of biological chemistry, 2009)
N(alpha)-tosyl-L-phenylalanine chloromethylketone (TPCK) has been widely used to investigate signal transduction pathways that are involved in gene expression and cell survival/cell death. However, contradictory effects of TPCK on apoptosis have been reported, and the underlying signaling events leading to TPCK-induced promotion or prevention of apoptosis are not fully understood. Here, we show that TPCK induces caspase-dependent apoptosis in Epstein-Barr virus (EBV)-transformed human B cell lines with release of pro-apoptotic proteins from mitochondria. TPCK treatment also results in down-regulation of the anti-apoptotic proteins, cIAP1, cIAP2, and HAX-1, and caspase-dependent cleavage of the anti-apoptotic proteins, Bcl-2 and XIAP. Quantitative PCR analysis confirmed that the TPCK-induced down-regulation of HAX-1 occurred at the transcriptional level, and experiments using the specific pharmacological inhibitor, Bay 11-7082, suggested that HAX-1 expression is subject to regulation by the transcription factor, NF-kappaB. B cell lines derived from patients with homozygous HAX1 mutations were more sensitive to TPCK-induced apoptosis when compared with normal donor cell lines. Furthermore, N-acetylcysteine effectively blocked TPCK-induced apoptosis in EBV-transformed B cell lines and prevented the down-regulation or cleavage of anti-apoptotic proteins. Taken together, our studies demonstrate that TPCK induces apoptosis in human B cell lines and exerts multiple effects on pro- and anti-apoptotic factors.